2019
DOI: 10.1097/md.0000000000017728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soft tissue injury and ulnar angulation on radial head instability in a Bado type I Monteggia fracture model

Abstract: The effects of soft tissue damage and ulnar angulation deformity on radial head instability in Monteggia fractures are unclear. We tested the hypothesis that radial head instability correlates with the magnitude of ulnar angular deformity and the degree of proximal forearm soft tissue injury in Bado type I Monteggia fractures.We performed a biomechanical study in 6 fresh-frozen cadaveric upper extremities. Monteggia fractures were simulated by anterior ulnar angulation osteotomy and sequential sectioning of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…[ 16 , 17 ] Moreover, certain authors recommend UO combined with open reduction of RHD. [ 18 20 ] Although all the authors reported improved outcomes after surgeries, complications are common, including radial head subluxation and instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16 , 17 ] Moreover, certain authors recommend UO combined with open reduction of RHD. [ 18 20 ] Although all the authors reported improved outcomes after surgeries, complications are common, including radial head subluxation and instability.…”
Section: Discussionmentioning
confidence: 99%
“…Over-distraction during the surgery increased the risk of delayed union or nonunion of osteotomy site, nerve palsy and postoperative compartment syndrome. [ 7 , 16 18 , 23 ] Besides, the gap of the osteotomy site should be filled with bone graft. [ 7 , 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…8,9 While many treatment options are available two important modalities commonly followed are 1) ulnar osteotomy with lengthening and 2)annular ligament reconstruction. The principle of Ulnar osteotomy is explained by Hayomi et al 10 in their biomechanical evaluation. When there is no anterior ulnar angulation, even with sectioning of the annular ligament and the capsule of the elbow joint there was no significant anterior displacement of the radial head.…”
Section: Discussionmentioning
confidence: 99%
“…From an ergonomic point of view, the mechanical behavior of the whole tissue will change dramatically if the soft tissue is damaged, which in turn suggests that biomechanical changes caused by STIs can be used to detect the severity of the injury [ 6 , 7 ]. In any event, all kinds of STIs must be considered when detecting and treating TFs [ 8 ]. Hence, research on the treatment of STIs and wound recovery has important practical value for improving patient outcomes and avoiding wound infection and necrosis.…”
Section: Introductionmentioning
confidence: 99%